Takhrij and Syarah Hadith of Agrotechnology Black Seed as Herbal Medicine - Vadilla Nopiyanti; Wahyudin Darmalaksana; Raden Roro Sri Rejeki Waluya Jati; Dikayani Dikayani (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this study is to discuss the hadith of the Prophet Muhammad, about black cumin. The method used in this research is a qualitative type through literature study and field studies with the approach of takhrij and sharah hadith agrotechnology. The results and discussion of this research are black cumin plants popular during the time of the Prophet Muhammad. and is known to have many properties. The conclusion of this study is the takhrij and syarah of the Prophet's hadith regarding black cumin plants as herbal medicine for all diseases in the era of the Prophet, not the treatment of all diseases in today's modern era.